Coupled Agricultural Subsidies in the EU Undermine Climate Efforts. Issue 4 (8th October 2020) - Jansson, Torbjörn; Nordin, Ida; Wilhelmsson, Fredrik; Witzke, Peter; Manevska‐Tasevska, Gordana; Weiss, Franz; Gocht, Alexander
Abstract: Subsidizing polluting industries generally leads to increased pollution locally. However, given the diversity of production technologies across countries and international trade, the global impact of unilateral policies is not a priori clear. We use the agricultural sector model CAPRI to simulate the impact of removing the voluntary coupled support for ruminants, presently permitted under the EU Common Agricultural Policy. We find that this reduces greenhouse gas emissions in the EU. However, emissions leakage significantly diminishes the global mitigation effect since about 3/4 of the reduction in the EU is offset by increased emissions in the rest of the world. Abstract : Related Content: Assessing the Environmental Impacts of Agricultural Policies Related Content: Reforming Agricultural Support for Improved Environmental Outcomes